IMPLEMENTASI METODE CLIENT CENTERED DALAM MENGATASI MASALAH PENYESUAIAN DIRI SANTRI DI MA PESANTREN MODERN DAAR AL ULUUM ASAHAN-KISARAN - Putri Ramadhani Sitorus (Al-Mursyid : Jurnal Ikatan Alumni Bimbingan dan Konseling Islam (IKABKI), 2019)
Adjustment is the ability to align oneself according to the conditions of the self and the demands of the environment around all the needs of themselves and the environmentassociated with responding to all kinds of conflicts, difficulties of life problems, frustration and others. Adjustment for students is very important, if students cannot adjust well, it causes the learning process to be hampered and students will experience other problems. This research is based on a phenomenon that occurs in the Islamic Boarding School Daar AlUluum Asahan-Kisaran, that there are some students who have adjustment problems. To overcome the problem of self-adjustment, BK Teachers use several effective methods, one of which is to do a client centered approach. The type of research used is qualitative research. Data collection techniques in this study were observation, interview and documentation. The data analysis technique used is to reduce data, present data and draw conclusions. The results of the study indicate that the client centered approach can overcome the problem of adjustment. This can be seen from the development of students toward a positive direction in the process of adjustment. Keywords : Client centered, Adjustment